Mass Spectrometry Imaging Reveals In Situ Behaviors of Multiple Components in Aerosol Particles. Issue 43 (11th August 2021) - Jiang, Yuming; Sun, Jie; Xiong, Caiqiao; Liu, Huihui; Li, Yuze; Wang, Xiao; Nie, Zongxiu
Abstract: The inhalation of atmospheric particles is deleterious to human health. However, as a complex mixture, tracing the behaviors of multiple components from real aerosol particles is crucial but unachievable by the existing methods. Here, taking advantage of the intrinsic fingerprints of elemental carbon (EC) and organic carbon (OC) in carbonaceous aerosol (CA) upon laser irradiation, we proposed a label‐free mass spectrometry imaging method to visualize and quantify the deposition, translocation and component variation of CA in organs. With this method, the heterogeneous deposition, clearance and release behavior of CA in lung, that more OC was released in parenchyma and OC was cleared faster than EC, was observed. The translocation of CA to extrapulmonary organs including kidney, liver, spleen and even brain was also verified and quantified. By comparing the ratio of OC to EC, an organ‐specific release behavior of OC from CA during circulation was revealed. In orthotopic lung and liver tumor, OC was found to penetrate more into tumor foci than EC. This technique provides deeper information for understanding the systemic health effects of aerosol particles. Abstract : A novel mass spectrometry imaging strategy to map and quantify the sub‐organ distribution and translocation of inhaled carbonaceous aerosol is reported. The method provides not only spatial biodistribution of carbonaceous aerosol at sub‐organ level, but also chemical changes of multiple components.